The Relationship between Politics and Religion (An Examination of the Concept of the Islamic State in the Perspective of Abu al-A'la Al-Maududi) - Taufiq, Muhammad (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
Islam, as a comprehensive and universal way of life, governs not only worship but also politics, statehood, economics, and social systems. Al-Maududi proposed an Islamic state based on the Qur’an, Sunnah, and practices of the companions, advocating for a caliphate system over a monarchy. He argued that the decline of Islamic politics began with the abandonment of the Khilafah system, emphasizing that true sovereignty belongs to God, with humans as executors of God’s will. A government enforcing God’s rules commands the people’s obedience. Al-Maududi outlined three state institutions: executive, legislative, and judiciary, functioning independently. The head of state, also the executive leader, must consult the Shura Council but isn’t bound by its majority opinion. The people must monitor the head of state, who can be dismissed if driven by personal desires. To prevent dictatorship, the head of state’s powers should be administratively limited, though Al-Maududi did not specify the term of office. In legislative elections, self-nomination is discouraged as it undermines political and social morale, contrary to Islamic law. Al-Maududi also opposed Muslim women holding key government positions or sitting in the Shura Council and People’s Council. Establishing an Islamic state is deemed essential to implement Allah’s commands in all life aspects.